If the body were a cetra, harmony would be his soul: On the soul-body relationship in Plato’s philosophy - Botter, Barbara (Revista Archai, 2020)
The aim of this text is to investigate if it is possible to attribute to Plato a dualistic conception of human nature, that is, whether the philosopher can be inscribed in the line of thinkers who establish the so-called “Mind-Body Problem”. In various passages of Platonic Dialogues we can see that the body and the soul constitute two different and quite incompatible natures. On the other hand, the relationship between body and soul is constitutive of human being and is unquestionable in the act of perception. Our study develops in three moments. At a first time we explain the reasons why it is justified to claim that there is in Plato’s Dialogues a difference between soul and body; afterwards, we analyze the relationship between soul and body just as an essential attribute of human nature; we bring about the investigation with the analysis of the “Plato’s pineal gland”, specifically, the element that allow us to consider the liaison between soul and body as a “dual relationship”, that is, not as an undifferentiated unit, nor as a juxtaposition of elements unrelated to each other. Our proposal consists in showing that the mathematical structure, proportional, harmonic and musical crosses all reality: the cosmic body and soul, as well as the human body and soul.